(untitled) (Revista Tecnológica, 2015)
It is proposed the use of ignition method to replace the digestion procedure in the total phosphorus quantification for aquatic macrophytes and its detritus. The remaining material from decomposition experiment was dried and submitted to ignition (550 ºC; 2 h). The same samples had their phosphorous contents quantified by colorimetric method that includes previous acid digestion. The phosphorous contents were also measured in the ash derived from ignition. For all samples (n = 104), the ignition method was less efficient, the average of global yield was 14.2%. The equivalence between these two procedures is stressed by the linear relationship with high r2 value (0.95).